Spin dynamics of S = 1/2 Heisenberg chains with a staggered transverse field: electron spin resonance studies (Review Article) - Zvyagin, S.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
In this article I review recent achievements on experimental studies of magnetic excitations in the copper pyrimidine dinitrate [PM–Cu(NO3)2(H2O)2]n (PM = pyrimidine), an S = 1/2 antiferromagnetic chain materialwith alternating g-tensor and the Dzyaloshinskii–Moriya interaction, by means of high-field electron spin resonance (ESR). Due to this alternation, in the 1D critical regime this material exhibits a field-induced gap. The excitation spectrum is formed by solitons and their bound states, breathers, and can be effectively described using the sine-Gordon model. With increasing temperature, the soliton-breather regime can be suppressed, resulting in a substantial evolution of ESR parameters. These changes can be described using a new theoretical concept recently proposed for S = 1/2 AF chains with a staggered transverse field. High magnetic field induces a transitioninto spin-polarized state with the excitation spectrum formed by magnons. Nonmonotonous behavior of the field-induced gap is observed in the vicinity of saturation field. The experimental data are compared with results of existing theoretical approaches, revealing an excellent agreement with the predictions.